q-Extensions for the Apostol Type Polynomials - Nazim I. Mahmudov; Marzieh Eini Keleshteri (Journal of Applied Mathematics)
The aim of this work is to introduce an extension for q-standard notations. The q-Apostol type polynomials and study some of their properties. Besides, some relations between the mentioned polynomials and some other known polynomials are obtained.